Multi-biomarkers approach to the assessment of the southeastern Mediterranean Sea health status: Preliminary study on Stramonita haemastoma used as a bioindicator for metal contamination - Bouzahouane, H; Barour,C; Sleimi, N; Ouali, K. (My University, 2018)
The present study aimed to evaluate the responses of different biochemicals parameters associated with environmental pollution in the digestive gland of the gastropod mollusc Stramonita haemastoma. Physiochemical parameters and trace metal elements (Copper (Cu), Zinc (Zn), Chromium (Cr), Cadmium (Cd) and Lead (Pb)) were measured in seawater. Spatiotemporal variations in reduced glutathione (GSH), malondialdehyde (MDA) and metallothionein (Mt) as well as the specific activities of glutathione Stransferase (GST) and catalase (CAT) were evaluated in digestive gland of this species during a one-year period in 2013e2014. Samples collection was conducted at three sites. The results obtained showed seasonal fluctuations in GST and CAT activities and in the rate of Mt content. In addition, intersite variations in GSH, MDA, Mt and CAT were recorded in individuals. Also, trace metal elements concentrations determined by season in the digestive gland revealed spatial and temporal variations for Cu and Zn but they are below the limit of detection for Cd and Pb. The highest values were generally recorded in spring for Cu and in winter for Zn. In this first regional study using in S. haemastoma as a model, the biomarkers measured were seen to be inducible parameters to evaluate the health state of the organism and the overall quality of the study sites.